Multiple susceptibility enhancer variants increasing ADD3 expression predisposes to biliary atresia risk - Han, Xinru; Pei, Haoyue; Bai, Meirong; Zhou, Ying; Chu, Xun (Frontiers in Genetics, 2026)
BackgroundNon-syndromic biliary atresia (BA) is a multifactorial disorder with a poorly understood genetic basis. We previously identified 154 BA-associated SNPs spanning the ADD3 locus, which harbors the most strongly associated common variants in Asian populations. The susceptibility SNPs are in high linkage disequilibrium, but the causal variants remain unidentified.MethodsUsing available databases, we predicted the regulatory potential of the 154 BA-associated SNPs. To functionally validate these findings, we assessed the enhancer activity of cis-regulatory elements (CREs) containing the risk variants using a dual-luciferase reporter assay. The role of ADD3 dysregulation in hepatobiliary development was investigated using zebrafish. The spatiotemporal expression pattern of the ADD3 ortholog in zebrafish embryos was mapped by in situ hybridization. Additionally, we performed mRNA overexpression and morpholino knockdown to examine the effects of perturbing ADD3 ortholog expression on zebrafish hepatobiliary development.ResultsAmong 154 associated SNPs, 28 clustered within 10 putative CREs with predicted enhancer function. In vitro allele-specific luciferase assays demonstrated enhancer activity in eight of these CREs, with risk haplotypes at three loci driving significantly higher activity than non-risk haplotypes (P < 0.05). The zebrafish add3a gene, an ortholog of human ADD3, was expressed in developing livers. Both overexpression and knockdown of add3a in zebrafish disrupted hepatobiliary function and development, resulting in gallbladder hypoplasia/agenesis and reduced intrahepatic bile duct density. These phenotypes closely recapitulate BA pathology observed in humans. Combined with our prior data linking risk alleles to heightened ADD3 expression and demonstrating ADD3 overexpression in BA livers, these results indicate that genetic variants drive ADD3 upregulation, thereby predisposing to BA development.ConclusionMultiple risk variants within enhancers upregulated ADD3 expression, which contributed to BA pathogenesis.